The cortical focus in childhood absence epilepsy; evidence from nonlinear analysis of scalp EEG recordings - Sarrigiannis, Ptolemaios G.; Zhao, Yifan; He, Fei; Billings, Stephen A.; Baster, Kathleen; Rittey, Chris; Yianni, John; Zis, Panagiotis; Wei, Hua-Liang; Hadjivassiliou, Marios; Grünewald, Richard (Elsevier, 2018)
Objective To determine the origin and dynamic characteristics of the generalised hyper-synchronous spike and wave (SW) discharges in childhood absence epilepsy (CAE). Methods We applied nonlinear methods, the error reduction ratio (ERR) causality test and cross-frequency analysis, with a nonlinear autoregressive exogenous (NARX) model, to electroencephalograms (EEGs) from CAE, selected with stringent electro-clinical criteria (17 cases, 42 absences). We analysed the pre-ictal and ictal strength of association between homologous and heterologous EEG derivations and estimated the direction of synchronisation and corresponding time lags. Results A frontal/fronto-central onset of the absences is detected in 13 of the 17 cases with the highest ictal strength of association between homologous frontal followed by centro-temporal and fronto-central areas. Delays consistently in excess of 4 ms occur at the very onset between these regions, swiftly followed by the emergence of “isochronous” (0-2ms) synchronisation but dynamic time lag changes occur during SW discharges. Conclusions In absences an initial cortico-cortical spread leads to dynamic lag changes to include periods of isochronous interhemispheric synchronisation, which we hypothesize is mediated by the thalamus. Significance Absences from CAE show ictal epileptic network dynamics remarkably similar to those observed in WAG/Rij rats which guided the formulation of the cortical focus theory.
Keywords: Absence; Zero-Lag; Nonlinear; Cortical focus theory; Thalamus; ERR causality test